Diversity of fish fauna in the Sembakung river, North Kalimantan, Indonesia. Issue 1 (November 2021) - Sawestri, S; Marini, M
Abstract: Sembakung river is an important inland fishery in terms of fish production in North Kalimantan, Indonesia. This river is connected to the State of Malaysia, where the upstream part of this river is in the state of Malaysia. The present study was conducted to inform the diversity of fish fauna in the Sembakung river. Fish samples were collected from ten sampling stations of the Sembakung river at Tarakan district in North Kalimantan, Indonesia from March to November 2019. A total of 55 species of fish under 20 orders and 35 families were recorded. Cypriniformes were most leading order constituting 32.73% of the total fish population followed by Siluriformes (18.18%), Anabantiformes (10.91%), Gobiiformes (9.09%), Carangaria (5.45%), Eupercaria (3.64%), and 1.82% for others ordo. Fishes in this river are seriously affected by the various kinds of human development interventions and activities, especially in the areas of agriculture, forestry, fisheries, industries, and transport. Estimates from these indices were indications of low fish species composition and richness and unevenness in the population of fish in the Sembakung river. For sustainability of fishery resources, an adequate knowledge of species composition, diversity, and relative abundance of water bodies must be understood and vigorously pursued. Therefore, there is a need for the conservation and sustainable management of the fisheries resources of the Sembakung water body by relevant agencies.